The Challenges of Religious Literacy The Case of Finland - Sakaranaho, Tuula; Aarrevaara, Timo 1961-; Konttori, Johanna (Cham Springer International Publishing, 2020)
Chapter 1. Introduction: Setting the stage -- Chapter 2. “There is Freedom of Religion in Finland, but…”: The Helsinki Mosque Debate -- Chapter 3. Laestadians in “the world”: reading the biggest Christian revival movement in Finland -- Chapter 4. Religious literacy and the governance of religious diversity in multi-faith schools: The Case of Islam -- Chapter 5. Islamic Divorce in Finland and Role of Mosques: Revisiting Binaries -- Chapter 6. Prevention of violent radicalization and extremism in Finland: the role of religious literacy -- Chapter 7. Conclusions: Religious literacy promotes absorptive capacity, inclusion and reflexivity in society.
This open access book presents religious literacy as the main explanatory factor when dealing with certain ethnic groups that attract stereotypes which gloss over other personal factors such as age, class, gender and cultural differences. It discusses freedom of religion, and the Christian revival movement. It examines religious literacy and religious diversity in multi-faith schools. It looks into the role of Mosques and Islamic divorce. Finally, it discusses the prevention of violent radicalization and extremism in Finland. Using recent data on Finnish secular society, the book promotes a new understanding which is needed with respect to popular and media portrayal of religion, or with respect to public discussion about religion. It addresses actors in civic society, public servants and higher education.
Open Access
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Church and education; Religion and sociology; Religion; Emigration and immigration